Surgical treatment of incisional tachycardia and atrial fibrillation in patients with mitral valve prosthesis: should we be scared? - O. V. Sapelnikov; O. A. Nikolaeva; D. F. Ardus; D. I. Cherkashin; I. R. Grishin; N. B. Shlevkov; A. A. Zhambeev; H. F. Salami; R. S. Akchurin (Патология кровообращения и кардиохирургия, 2018)
Mitral valve disease, including dysfunction of the mitral valve, is often accompanied by atrial fibrillation. Among the patients with prosthetic mitral valves, atrial fibrillation occurs in 30–50% cases. Development of atrial arrhythmias and incisional tachycardia in the early and late postoperative periods can significantly influence patients’ rehabilitation and prognosis. Our clinical case describes a patient with a mechanical mitral valve and incisional tachycardia, which led to progression of heart failure and reduced left ventricular systolic function. The patient underwent catheter ablation with non-invasive myocardium mapping. The case reveals the potentials of treatment of incisional tachycardia and atrial fibrillation, which do not respond to drug therapy. Modern methods of visualization enable the cardiac surgeons to reduce possible intraoperative risks and development of complications in this group of patients.